Pelaksanaan BPJS Kesehatan Menurut Pandangan Hukum Positif Dan Hukum Islam Di Indonesia - Nandang Ihwanudin (STAI Siliwangi Bandung, 2015)
Validity period of BPJS in 2011 gave the consequences to change a number of social security institutions in Indonesia that insurance agencies guarantee health, PT Askes and social security institutions employment, PT Jamsostek Transformed into BPJS. On January 1, 2014, PT Askes transformed into BPJS Health, then on July 1, 2015 PT Jamsostek transformed into BPJS Employment. BPJS in the implementation of Health, there are pros and cons with Islamic law, so that through ijtima MUI in July 2015 concluded that the fund management BPJS deemed incompatible with Islamic law. In this paper, the authors will describe the implementation of the BPJS Health in the view of Islam. Whether implementation has Shari'a compliant or not? If not, what are things that become the reason? What are the consequences and solutions for Moslem people who want to become a membership BPJS in accordance of Islamic law? Results of this paper can be concluded that the Organization of the BPJS considered incompatible with Islamic principles because they contain an element of uncertainty (gharar) because of contract and ownership of the premiums (contributions) is not clear, has an element of gambling (gambling) because there is an element of profit and loss, and usury.